The Kushner-Stratonovich stochastic method for a master robot of a tele-robotic system: beyond extended Kalman filtering. (5th April 2019) - Hirpara, Ravish H.; Sharma, Shambhu N.
The surgical robotic system, a tele-robotic system, comprises the operator, master-slave configuration in combination with the object. For the estimation and control of the surgical robotic system, the master-slave set up is the subject of greater robotic research activities as well as has proven promising. In this paper, the multi-dimensional stochastic differential equation as well as the higher-order nonlinear stochastic filter beyond extended Kalman filtering for a master robot of the surgical robotic system are developed. The higher-order nonlinear filtering preserves the greater qualitative characteristics of nonlinear stochastic systems by accounting observation correction terms in stochastic evolution equations. First, the Lagrangian mechanics is exploited to develop the vector stochastic model of the master robot. Secondly, this paper utilises the Kushner-Stratonovich equation, for filtering of the master robot noise equations. This paper demonstrates comparison between the higher-order Kushner-Stratonovich filter, extended Kalman filter and true state trajectories as well.